2017
DOI: 10.1016/j.scitotenv.2017.01.190
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in freshwater and terrestrial environments: Evaluating the current understanding to identify the knowledge gaps and future research priorities

Abstract: Lahive, Elma; Svendsen, Claus. 2017. Microplastics in freshwater and terrestrial environments: evaluating the current understanding to identify the knowledge gaps and future research priorities.Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.Crown

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
1,141
0
43

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 2,754 publications
(1,198 citation statements)
references
References 155 publications
14
1,141
0
43
Order By: Relevance
“…There is no defined size for a particle categorized as "microplastic", but an upper limit of 5 mm is generally agreed upon in the literature [4,5]. Particles are present in terrestrial, freshwater, and marine environments (for example, [5]) but have also been observed in the remotest areas of the world [6]. Studies proved plastic particle appearance in deep-sea sediments [7] as well as trapped in Arctic Sea ice [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is no defined size for a particle categorized as "microplastic", but an upper limit of 5 mm is generally agreed upon in the literature [4,5]. Particles are present in terrestrial, freshwater, and marine environments (for example, [5]) but have also been observed in the remotest areas of the world [6]. Studies proved plastic particle appearance in deep-sea sediments [7] as well as trapped in Arctic Sea ice [8].…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to sunlight, wind, and the chemical environment, the material alters and breaks down to debris of a few micrometres in size, which can easily be dispersed. Little is known about the biological effects, such as organism interaction with and ingestion of microplastics [9], but particle consumption has been widely observed in marine species [6], and particles may be retained in the gut or even cross the gut wall to be translocated within the body [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, recent studies have also been investigating this issue with aims to standardize methods for macro-and microplastics extraction in locations such as sediment (Van Cauwenberghe et al 2015;Besley et al 2017), and fresh and seawater (EerkesMedrano et al 2015;Horton et al 2017), as well as characterizing and analyzing their distribution (Graca et al 2017;Mai et al 2018). In addition, the characteristics of polymeric chemical bonds that confer plastics their interesting manufacturing properties also make them susceptible to degradation, consequently losing their mechanical properties (Crawford and Quinn 2017b).…”
Section: Introductionmentioning
confidence: 99%